Quality of Clinical Nursing Education Programme in Ghana: Preceptors' Perspectives - Gilbert Ti-enkawol Nachinab; Susan Jennifer Armstrong (Diponegoro University, 2022)
Background: Clinical education is an important component of the training of nursing students. Preceptors play a key role in the clinical education of nursing students by providing support for the students during clinical placement. There is dearth of studies in the Ghanaian context that has assessed preceptors' perception of clinical nursing. Purpose: The purpose of this study was to assess preceptors' perceptions of the quality of clinical nursing education in Northern Ghana. Methods: This study was a cross-sectional survey conducted using an already existing questionnaire. Three hundred and nineteen (319) preceptors recruited from three hospitals participated in the study. A proportional quota sampling technique was used to allocate the sample size to the three hospitals and a simple random sampling technique was used to select the participants. The data were analysed using Stata version 15 and the results were presented using descriptive and inferential statistics. Results: The study findings indicate that the preceptors' generally perceived that the quality of clinical placement area and clinical assessment were slightly above average as they scored each of them 2.30 on a scale of 0-4 (95% CI:2.21-2.39). The preceptors also perceived that the quality of clinical teaching and learning was average as the they scored it 2.04 on a scale of 0-4 (95% CI:1.95-2.13). Also, the preceptors had a lower level of agreement, 1.75 on a scale of 0-4 (95% CI:2.15 -2.45) regarding teaching and development of the students being the responsibility of only the university. Conclusion: Preceptors perceived that nursing education institutions and clinical facilities need to work together to improve clinical nursing education. This calls for the need for an effective collaboration between clinical facilities and nursing education institutions to develop training programmes for preceptors to improve their skills in clinical teaching and clinical assessment of students.